Epidemiologic changes in bloodstream infections in Andalucía (Spain) during the last decade. (February 2021) - Martínez Pérez-Crespo, P.M.; López-Cortés, L.E.; Retamar-Gentil, P.; García, J.F. Lanz; Vinuesa García, D.; León, E.; Calvo, J.M. Sánchez; Galán-Sánchez, F.; Natera Kindelan, C.; del Arco Jiménez, A.; Sánchez-Porto, A.; Herrero Rodríguez, C.; et al.
Abstract: Objectives: During the last decade, some changes in the epidemiology of invasive infections have been reported; however, specific studies with patient-level data are scarce. The aim of this study was to describe and evaluate the epidemiologic changes in bloodstream infections (BSI) during the last decade in Andalucía, Spain. Methods: Data from two prospective cohorts of BSI in adults with the same methodology performed 10 years apart in 11 hospitals (eight tertiary and three community) in Andalucía, Spain, were compared; the 2006–7 cohort study was performed between October 2006 and March 2007, and the 2016–17 cohort study was performed between October 2016 and March 2017. Population-based incidence rates were calculated and extrapolated for 1 year. Relative risk ratios were calculated between the 2 periods. Multivariate analyses were performed by logistic regression. Results: Overall, 1262 episodes of BSI were included, 563 (44.6%) in 2006–7 and 699 (55.3%) in 2016–17. Multivariate models selected the following changes in patients' features in 2016–17, after controlling for type of acquisition: higher age (odds ratio (OR) = 1.02; 95% confidence interval [CI] 1.01–1.03), lower urinary catheter (OR = 0.37; 95% CI, 0.26–0.48) and lower Pitt score (OR = 0.76; 95% CI, 0.71–0.82). Adjusted estimations considering patients' features and exposure to procedures showed a reduction in coagulase-negative staphylococci (OR = 0.47; 95% CI, 0.32–0.69), and an increase in Proteus spp. (OR = 3.12; 95% CI, 1.18–8.23) and Candida spp. (OR = 3.01; 95% CI, 1.03–8.86). Conclusions: We found relevant epidemiologic changes in BSI in our area, including rates, frequency of acquisition types, changes in patient's profiles and aetiologic agents.